AN ANALYSIS OF FIGURATIVE LANGUAGE IN THE SONG LYRIC BY ADELE’S - Dewa Ayu Made Diah Kumala Dewi; I Gde Agoes Caskara Surya Putra (CV. Multi Kreasi Media, 2022)
This research is entitle An Analysis of Figurative language in the Song Lyrics By Adele’s. Figurative language is a language that is usually used to analyze in depth, espicially in song lyrics. According to Anderson (2005:4) figurative language is used imaginatively. The perpose of this research is to find out the parts of figurative language and to know more about the types of figurative language used in Adel’s song lyrics. This study used descriptive qualitative method. According to Sugiono (2016:9) qualitative method is research methods used to examine natural object. Collecting the data by listening to You Tube, Spotify, or other applications. Data can write song lyrics that contain meaning in figurative language. For several types of figurative language, the writer gets six types of figurative language there are metaphor, simile, paradox, personification, symbol, and hyperbole. And can analyzed the types of figurative language because of the song lyrics which contain the several parts of meaning in figurative language. Readers can also find out the significance of Adele’s song lyrics and can find out more about the parts in figurative language.